ANALISIS PROYEK PEMBANGUNAN KANTOR DENGAN MENGGUNAKAN C.P.M. DI PT KASOEM HEARING CENTRE - RUHIMAT RUHIMAT; BUDI SUMARTONO; HARI MOEKTIWIBOWO (JURNAL TEKNIK INDUSTRI, 2021)
PT. Kasoem Hearing Center is one of companies focusing on hearing aid and optic which is located in Jl.Cikini Raya no.18 Jakarta Pusat. A company often get a problem when finishing the project because it is not appropriate with the time agreed before. Therefore, analysis of project time optimalization is needed to know how long the project is finished, and to find out existence of time acceleration possibility of the project implementation by using CPM. Steps in analyzing of PT. Kasoem Hearing Centre office development project are: deciding stages of activity, changing of chart, track lane, critical path, calculating the cost, accelerating of processing time, and counting the project using CPM. Forms of job network of PT. Kasoem Hearing Centre Office Project are: Preparation & Destruction Job – Earthworks, excavation, fill the ground, installation – Structural work & amp; reinforced concrete – Wall work – Roof job – Electrical installation work A – Floor job A – Ceiling job A – Door and window job A – Finishing, painting, etc. B=A-B-C-D-F-H-L-N-O-Q-R-S-U-V (critical path), with optimal time duration of Office development project is 159 days from 174 days normal time. Based on researching result, researcher gives suggestion as follows: The Project Team should use CPM in implementing Office development project. Because the faster completion time of Office development project, then the office also can be operated to support activity needs and employee operational.Keywords : Project, CPM, Project Time, Project Costs